Identification of MX2 as a Novel Prognostic Biomarker for Sunitinib Resistance in Clear Cell Renal Cell Carcinoma - Wei, Yuang; Chen, Xinglin; Ren, Xiaohan; Wang, Bao; Zhang, Qian; Bu, Hengtao; Qian, Jian; Shao, Pengfei (Frontiers in Genetics, 2021)
Background: Antiangiogenic agents that specifically target vascular endothelial growth factor receptor (VEGFR), such as sunitinib, have been utilized as the standard therapy for metastatic clear cell renal cell carcinoma (ccRCC) patients. However, most patients eventually appear no responses to the targeted drugs, and the mechanisms for the resistance remain unclear. This study is aimed to identify pivotal molecules and their potential functions involved in this adverse event in ccRCC treatment. Methods: Two data sets GSE64052 and GSE76068 were obtained from the gene expression omnibus (GEO) database. The DEGs were identified using the limma package in R software. The gene set enrichment analysis (GSEA) was conducted using clusterProfiler package. A Protein-protein interaction (PPI) network was build using the STRING database and Cytoscape software. Kaplan-Meier survival curves were plotted using R software. Four miRNA-mRNA databases were applied to predict the potential miRNAs. qRT-PCR and Western blot were used to detect the MX2 expression in RCC cell lines. All statistical analyses were performed using R version 3.6.1 and SPSS 23.0. Results: 760 DEGs were derived from two data sets in GEO database and 5 hub genes were identified, among which high-level MX2 exhibited a pronounced correlation with poor overall survival (OS) in sunitinib-resistant ccRCC patients. Clinical correlation analysis and Gene Set Variation Analysis (GSVA) on MX2 showed that the upregulation of MX2 was significantly related to the malignant phenotype of ccRCC, and it was involved in several pathways and biological processes associated with anticancer drug resistance. A total of 42 miRNAs were predicted by comparing several miRNA target databases and the miRNA-MX2 regulatory network was constructed. Finally, qRT-PCR and Western blot revealed that MX2 was distinctly up-regulated in sunitinib-resistant RCC cell lines. Conclusion: Our study proved for the first time that MX2 is a potent indicator for sunitinib resistance and prognosis in targeted agents-treated ccRCC patients, and it could be a potential target for TKIs-resistant ccRCC treatment.